Citrus Snow Scale Unaspis citri (Comstock) (Insecta: Hemiptera: Coccoidea: Diaspididae) - Courtney R. Buckley; Amanda Hodges (EDIS)
This document provides an overview of the citrus snow scale, Unaspis citri, an armored scale insect affecting citrus crops. It details the insect’s biology, life cycle, and distribution, highlighting its impact on citrus production in Florida. The document also discusses the economic significance of citrus snow scale infestations and outlines management strategies, including biological, cultural, and chemical controls. Emphasis is placed on the importance of monitoring and controlling this pest to prevent economic damage to citrus groves.